Bond behaviour of CFRP-strengthened ECC using Response Surface Methodology (RSM). (June 2020) - Lye, Hui Li; Mohammed, Bashar S.; Liew, M.S.; Wahab, M.M.A.; Al-Fakih, Amin
Abstract: Multi-layers of carbon fibre reinforced polymer (CFRP) were used to strengthen engineered cementitious composites (ECC) to study their effects on flexural and tensile strengths. Response Surface Methodology RSM was used to obtain the number of trial mixes. A total of 13 mix designs were suggested with two variables: polyvinyl alcohol (PVA) fibre (0.5 %, 1.25 % and 2.0 %) and number of CFRP (1, 3 and 5 layers). The result showed that the flexural strength of specimens with 0.5 % and 2.0 % PVA fibre was enhanced by more than 40 % and 55 %, respectively, when the CFRP layers were increased to 3 and 5 layers, which subsequently increased the absorption energy of the specimens by more than 20 %. Moreover, the tensile strength of the specimens with 1.25 % and 2.0 % PVA fibre improved by 31 % and 61 %, respectively, after these have been strengthened with 3 and 5 CFRP layers. To validate these results, the experimental responses were analysed and optimised using RSM. The coefficient of determination R 2 yielded high values at 0.9647 and 0.9747, which indicated the good agreement of the proposed model to the experimental responses. Consequently, a quadratic model and a 2FI (two-factor interaction) model were developed to estimate the bond behaviour of CFRP-strengthened ECC. Based on these models, the best solution of CFRP strengthening with respect to the present study is to use 2 % PVA fibre and 5 layers of CFRP.